Hepatoprotective and antioxidant effects of Glycyrrhiza glabra extracts against TCDD-induced hepatocyte damage in Jian carp (Cyprinus carpio var. Jian) - Du Jinliang; Cao Liping; Jia Rui; Liu Yingjuan; Shen Yujin; Yin Guojun (浙江大学学报. 农业与生命科学版, 2015)
In recent years, the mechanism of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) toxicity has been a focal point in research. Generally it enriched in adipose tissue, and gradually amplified through food chains. It is seriously interfered with the normal function of the endocrine system of the organism, and displayed a wide spectrum of toxic effects, including dermal toxicity, reproductive toxicity, immunotoxicity and hepatotoxicity. The current research about the toxic mechanism of TCDD was mainly focused on the oxidative stress reaction, which was considered to be playing an important role in TCDD toxic research. Normally, the production and elimination of activated oxygen through the antioxidant system was in a balanceable and dynamic state. The antioxidant system could prevent excessive reactive oxygen species causing oxidative stress, keep the body balance, maintain the normal structure and function of cells. TCDD combined with aromatic hydrocarbon receptor and entered the nucleus, which changed the mRNA transcription of target gene, caused adverse change in the activity of enzymes and proteins, produced a series of oxidative stress reaction. Chinese medicinal herbs had been widely used in animal disease prevention due to their characteristics of rich bioactive components, free pollution, low side effects and immune enhancement. Many studies had reported that natural antioxidants were efficacious in preventing oxidative stress-related liver pathologies due to particular interactions and synergisms. Glycyrrhiza glabra extracts (GGE) was one of the common traditional Chinese herbal medicine, it could adjust the immunity, and had anti-tumor, anti-virus, antioxidant effects and so on. Although numerous studies had reported its beneficial effects on mammals, there was a lack of reports on its function in aquatic animals.The aim of this study was to evaluate the hepatoprotective and antioxidant effects of GGE on the TCDD-induced liver injury in Jian carp (Cyprinus carpio var. Jian).Jian carp were fed with diet containing 3 doses of GGE (0.1, 0.5 and 1.0 g/kg diet) for 60 days before a single intraperitoneal injection of TCDD (0.6 μg/kg), 72 h after TCDD injection, blood and liver samples were taken for biochemical analysis.The results showed that GGE at 1.0 g/kg diet for 60 days prior to TCDD intoxication significantly reduced the elevated activities of ALT, AST, LDH, AKP and increased the reduced levels of total protein (TP), albumin (Alb) in the serum, markedly inhibited the reduction of the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), total antioxidant capacity (T-AOC), and reduced the malondialdehyde (MDA) formation in liver tissue. Meanwhile, histopathological observation also showed that GGE can significantly relieve TCDD induced liver injury.It is concluded that GGE exhibited protective effect against TCDD-induced hepatotoxicity in fish, which is likely related to its antioxidant activity, and it is suggested that GGE may potentially be used as a hepatoprotective agent for fish liver injury.